Quality control in manuscript acquisition and assessment as prerequisites for quality book production in South-West, Nigeria (2016)
Book production is a complex process which requires a multiplicity of skills, expertise and input from different professionals. Many books published in Nigeria are low in quality in terms of content and physical appearance when compared with foreign publications. Consequently, most book users prefer imported books. The crucial factor of content quality therefore constituted the problem of this research. The study focused on quality control in manuscript acquisition and assessment for book production in South-West Nigeria. The study adopted survey method using the questionnaire as the main instrument for data collection. The study population was 62 publishing firms in South-West Nigeria as listed in the registered members’ directory of the Nigerian Publishers Association (NPA) published in December, 2014 while the sample for the study was 50 %. Findings showed that many publishing firms did not employ writing workshop approach for manuscripts acquisition; many also relied on external assessors to determine the viability of manuscripts without providing evaluation criteria. The study recommended that publishers in South-West Nigeria should incorporate Quality Control (QC) measures into manuscript acquisition and assessment for quality enhancement and profitability.